Radio Galaxies at TeV Energies - Cameron Rulten (Galaxies, 2022)
Unlike blazars, radio galaxies have jets that are misaligned relative to our line-of-sight. This misaligned geometry provides us with a unique view of both the jet and super massive black hole. To date, four radio galaxies have been detected at TeV energies with an additional two active galactic nuclei shown to exhibit both radio galaxy and BL Lac-type properties. TeV observations of radio galaxies have revealed these objects to be fascinating, displaying ultra-fast variability and often relatively hard spectral energy distributions. This work aims to provide a review of the current state of radio galaxy observations within the context of very-high-energy <semantics>γ</semantics>-ray astronomy, while also highlighting that radio galaxies are excellent targets for multi-wavelength observations. A number of motivations for the continued study of radio galaxies are provided, and these are discussed with a focus on the key observational results, including implications for future observations with next-generation instruments soon to be operational.